2000
DOI: 10.1001/archinte.160.20.3082
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Age and Lifestyle Factors in Relation to Community-Acquired Pneumonia in US Men and Women

Abstract: Smoking and excessive weight gain are risk factors for CAP among men and women, and physical activity was inversely associated with risk of CAP only among women. The incidence of CAP could possibly be decreased by lifestyle factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
301
10
14

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 309 publications
(341 citation statements)
references
References 50 publications
16
301
10
14
Order By: Relevance
“…Steroid exposure has rarely been addressed as a potential risk factor for pneumonia in the general population (38)(39)(40)(41)44). To our knowledge, glucocorticoid dosage has not been demonstrated to be predictive of pneumonia risk in any previous study.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Steroid exposure has rarely been addressed as a potential risk factor for pneumonia in the general population (38)(39)(40)(41)44). To our knowledge, glucocorticoid dosage has not been demonstrated to be predictive of pneumonia risk in any previous study.…”
Section: Discussionmentioning
confidence: 80%
“…The pathophysiologic explanation for this finding is, however, incompletely understood. A number of studies have also established smoking history as a risk factor for pneumonia (42)(43)(44)(45).The relevant mechanisms that have been proposed include decreased ciliary and respiratory epithelial function, as well as defects in cellular and humoral immunity (44,46). Interestingly, smoking entered the univariate model (Table 3), but was not predictive by multivariate analysis (Table 5) because of its correlation with preexisting pulmonary disease (which it may have caused).…”
Section: Discussionmentioning
confidence: 99%
“…A radiology report of a pulmonary infiltrate confirmed the presence of pneumonia in 82 percent of the cases. [3] After the first two years of this study, medical records were obtained from all women who reported radiologically diagnosed pneumonia. After reviewing records from a sample of 99 confirmed cases, only one was potentially hospital-acquired.…”
Section: Identification Of Cases Of Pneumoniamentioning
confidence: 99%
“…Risk factors for pneumonia include smoking, chronic obstructive pulmonary disease, alcohol abuse, and age. [3] Surprisingly, little research exists on the dietary risk factors that may impact on community-acquired pneumonia risk other than malnutrition. [3][4][5] Essential fatty acids (alpha-linolenic and linoleic acids), non-essential fatty acids (palmitic and oleic acids), eicosapentanoic acid or EPA, and docosahexanoic acid or DHA may impact the risk of community-acquired pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…heart, renal and lung diseases, low body mass index [BMI] and previous respiratory infection) and environmental factors (e.g. second-hand smoke and exposure to gases, fumes and chemicals) [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%